Improved the AlGaN-Based Ultraviolet LEDs Performance With Super-Lattice Structure Last Barrier - Qian Chen; Jun Zhang; Yang Gao; Jingwen Chen; Hanling Long; Jiangnan Dai; Zi-hui Zhang; Changqing Chen (IEEE Photonics Journal)
In this paper, a structure of super-lattice structure last barrier (SLSLB) is proposed, which can be applied into the AlGaN-based ultraviolet light-emitting diodes (LEDs) for improving the injection of both electrons and holes. Several other SLSLBs are also designed and compared in this work, and according to the simulated results, we find that the LED with SLSLB of diminishing thickness (SLSLB-D) possesses the highest internal quantum efficiency and the smallest efficiency droop. The SLSLB-D can effectively reduce the electron concentration at the interface between the last barrier (LB) and electron block layer (EBL), which relieves the leakage of electrons. Moreover, the best hole injection capability for the LED with SLSLB-D also contributes to the improved optical performance.